A Combination of Lactic Acid Bacteria and Molasses Improves Fermentation Quality, Chemical Composition, Physicochemical Structure, in vitro Degradability and Rumen Microbiota Colonization of Rice Straw - Chen, Xu; Ma, Yulin; Khan, Muhammad Zahoor; Xiao, Jianxin; Alugongo, Gibson Maswayi; Li, Shengli; Wang, Yajing; Cao, Zhijun (Frontiers in Veterinary Science, 2022)
Aims: This study aims to evaluate the effect of lactic acid bacteria (LAB) and LAB-molasses (LAB + M) combination on the fermentation quality, chemical composition, physicochemical properties, in vitro degradability of rice straw and the characteristics of rumen microbial colonization on rice straw surface. Methods and Results: Three pretreatments, including control (not treated, Con), were treated with LAB or LAB + M. The results showed that both LAB and LAB + M treatments altered the physical and chemical structure of rice straw and were revealed by Scanning electron microscopy (SEM) and X-ray diffraction analysis (XRD) spectroscopy, respectively. Moreover, Both LAB and LAB + M pretreated rice straw increased the crude protein (CP) content, dry matter (DM) recovery and in vitro digestibility and decreased the pH value, neutral detergent fiber (NDF), and acid detergent fiber (ADF) contents. The LAB + M pretreated rice straw increased the gas production (GP72) and rumen microbial colonization on the rice straw surface. Conclusions: It is observed that LAB + M treatment could increase digestibility and the rumen microbial colonization on the rice straw surface. Therefore, LAB + M treatment can provide an alternative strategy to improve the quality of rice straw. Significance and Impact of the Study: This study provides an optimal pretreatment to improve the rice straw digestibility and rumen microbial colonization.